Persepsi Jamaah Terhadap Pemberdayaan oleh Takmir Masjid di Kota Madiun Jawa Timur - Rosidin Rosidin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
Mosques have very significat roles in the developmen of pilgrims’ spiritual living as well as the other aspects. The article aims to analyze the level of empowerment conducted by the development committe and dimension should be prioritized. The study used quantitative research design. The validity and realibility tests remained 21 items as for being used as the research tool. The number of samples was 100 pilgrims chosen randomly. The enpowerment consisted of four dimension, namely : accesbility, participation, accountability, and local organization. The data werw analyzed using excell. The study resulted : (1) The empowerment of pilgrims in Madiun City categoryzed as good (value = 75, 38); (2) All the empowerment dimensions were at good levels, in whice the lowest value was found in the local organization dimension; (3) The local organization dimension value 72, 00, meant it should be priorityzed without  neglecting the other dimensions